Intramural esophageal tumors - Łochowski, Mariusz; Kozak, Katarzyna; Rębowski, Marek; Kozak, Józef (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2016)
Introduction : Intramural esophageal tumors (IET) are located between unchanged mucous membrane and muscularis mucosae. They can be both benign and malignant. Aim : To evaluate diagnostic and therapeutic difficulties of IET. Material and methods : During the years 2010–2015, 11 patients with IET were treated in our clinic. Diagnostics included gastroscopy, computed tomography of the chest, endoscopic ultrasound (EUS) guided fine needle biopsy, and positron emission tomography (PET) of the esophagus in cases with no histopathological confirmation. Results: Based on the conducted analysis we diagnosed 1 case of gastrointestinal stromal tumor (GIST), 1 case of adenocarcinoma, and 2 cases of esophageal cysts. In another 7 cases radiological images resembled leiomyoma but with no histopathological confirmation. Esophagectomy was performed in 2 cases of malignant tumors and 1 case of a large benign tumor. In other cases surgical enucleation of tumors was performed. Postoperatively we diagnosed 6 cases of leiomyoma, 1 case of schwannoma, 2 esophageal cysts, 1 case of GIST and 1 of esophageal cancer. Conclusions: Intramural esophageal tumors is a very diverse group of tumors, both malignant and benign. In every case of IET we should seek histopathological conformation. Treatment of IET depends on localization, size and histopathological type of lesion.